Mathematics Learning Syntax Model Using Open-Ended Problem Solving To Develop Students’ Creativity - I Ketut Suastika; Dyah Tri Wahyuningtyas (Pancaran Pendidikan, 2017)
The focus of this research was to develop a syntax model for Mathematics learning using open-ended problem solving that can develop students’ creativity. The emphasis on creativity development was done since the curriculum and the experts also emphasize it. This can be understood since someone with high creativity can quickly make innovations or new breakthroughs. The design research used in this study followed Plomp’s design research (2007), which consisted of: (1) preliminary research phase; (2) prototyping phase; and (3) assessment phase. The syntax model produced in this research has five phases, namely: (1) introduction; (2) concept tracking; (3) open-ended problem presentation; (4) presentation of work; and (5) closing.